Studi Empiris Tentang Dampak Penggunaan Televisi Digital Terhadap Partisipasi Politik Generasi Z Di Desa Campang Tiga Ulu, Kecamatan Cempaka, Kabupaten Oku Timur - Septa Icmaza; Sumaina Duku; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2025)
This study discusses the impact of digital television usage on the political participation of Generation Z in Campang Tiga Ulu Village, Cempaka Subdistrict, OKU Timur Regency, within the context of the 2024 General Election. Generation Z, as a group of young voters born and raised in the digital era, holds significant potential in shaping the direction of democracy. Digital television, as a result of the migration from analog broadcasting, is expected to serve as an effective medium for political information. This research employs a descriptive quantitative approach by distributing questionnaires to 94 respondents from Generation Z who are eligible to vote. Data analysis was conducted using the normality test, Spearman correlation test, and coefficient of determination test. The findings indicate that there is no significant relationship between the use of digital television and the political participation of Generation Z (r = -0.069; sig. = 0.512), with a contribution effect of 0.48%. These results suggest that digital television has not had a substantial influence on the political engagement of young people. Other factors such as social media, social environment, and political education are more likely to shape their political awareness. Therefore, more relevant and engaging political communication strategies are needed to encourage the active participation of young generations in democracy.